PENGARUH MODEL PEMBELAJARAN CLIS BERBASIS OUTDOOR STUDY TERHADAP KEMAMPUAN LITERASI SAINS SISWA KELAS V SEKOLAH DASAR - Adhari; Emi Sulistri; Erdi Guna Utama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aims of this research are, 1. To find out the difference in the scientific literacy abilities of students who are taught using the outdoor study-based CLIS learning model and students who use the conventional learning model, 2. To find out how much influence the outdoor study-based CLIS learning model has on scientific literacy abilities fifth grade elementary school students. The type of research used is quantitative quasi-experimental and the research design is Posttest-Only Control Group Design. Sampling uses a saturated sampling technique. The research sample of VB class students was 30 students. The instrument used in the research was a test sheet for students' scientific literacy abilities. The data analysis technique uses a two-sample t test and effect size. Research result; 1) There is a difference in the scientific literacy abilities of students who use the Outdoor Study Based CLIS Learning Model with students who are taught using conventional methods in VB class, the calculation results show = 3.44 and = 2.00; 2) The CLIS Learning Model Based on Outdoor Study has a big influence on the scientific literacy abilities of fifth grade elementary school students, with an effect size calculation result of 0.60.